The (De)confinement Transition in Tachyonic Matter at Finite Temperature - Adamu Issifu; Francisco A. Brito (Advances in High Energy Physics)
We present a QCD motivated model that mimics QCD theory. We examine the characteristics of the gauge field coupled with the color dielectric function (G) in the presence of temperature (T). The aim is to achieve confinement at low temperatures T<Tc, (Tc is the critical temperature), similar to what occurs among quarks and gluons in hadrons at low energies. Also, we investigate scalar glueballs and QCD string tension and effect of temperature on them. To achieve this, we use the phenomenon of color dielectric function in gauge fields in a slowly varying tachyon medium. This method is suitable for analytically computing the resulting potential, glueball masses, and the string tension associated with the confinement at a finite temperature. We demonstrate that the color dielectric function changes Maxwell’s equation as a function of the tachyon fields and induces the electric field in a way that brings about confinement during the tachyon condensation below the critical temperature.